2019
DOI: 10.1101/691972
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of D. melanogaster ARC1 reveals a repurposed molecule with characteristics of retroviral Gag

Abstract: 18The tetrapod neuronal protein ARC and its D. melanogaster homologue, dARC1, have 19 important but differing roles in neuronal development. Both are thought to originate 20 through exaptation of ancient Ty3/Gypsy retrotransposon Gag genes, with their novel 21 function relying on an original capacity for self-assembly and encapsidation of nucleic 22 Keywords: ARC; Gag; CA; Neuronal development; TY3/Gypsy. 33 34 lineages of Ty3/Gypsy, since dARC1 clustered with insect Ty3/Gypsy retrotransposons 60 and tetrapod … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 63 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…111 Interestingly, the mammalian Arc N-lobe in complex with ligand adopts a βstrand structure similar to dArc N-lobe. 78,111 As discussed in Hallin et al, 86 this raises the possibility that dArc N-lobe could bind peptide ligands under conditions that liberate the N-terminal strand, albeit with a binding specificity different from that of mammalian Arc N-lobe. 111 Another recent study performed structural characterization of the dArc lobe domains.…”
Section: Drosophila Arc Proteins and Capsid Structuresmentioning
confidence: 98%
See 3 more Smart Citations
“…111 Interestingly, the mammalian Arc N-lobe in complex with ligand adopts a βstrand structure similar to dArc N-lobe. 78,111 As discussed in Hallin et al, 86 this raises the possibility that dArc N-lobe could bind peptide ligands under conditions that liberate the N-terminal strand, albeit with a binding specificity different from that of mammalian Arc N-lobe. 111 Another recent study performed structural characterization of the dArc lobe domains.…”
Section: Drosophila Arc Proteins and Capsid Structuresmentioning
confidence: 98%
“…81,110 A high-resolution crystal structure of the dArc1 CA reveals a homodimer and a dimerization interface in the C-lobe homologous to retroviral CA. 78 In another major advance, single particle cryo-EM was used to resolve the structure of dArc capsids. 110 The dArc proteins both assemble into icosahedral capsids, with the capsid shell formed by 240 copies of the dArc CA.…”
Section: Drosophila Arc Proteins and Capsid Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, reduced Arc expression impairs learning ability in rodents (Guzowski et al, 2000; Shandilya and Gautam, 2020), and defects in human Arc have been linked to neurological and neurodevelopmental disorders, including Alzheimer’s disease (Bi et al, 2018), autism spectrum disorders (Alhowikan, 2016), and schizophrenia (Fromer et al, 2014). Both mammalian Arc and fly Arc1 encode retroviral group-specific antigen-like amino acid sequences, and are predicted to have independently derived from ancient Ty3/Gypsy retrotransposons (Ashley et al, 2018; Campillos et al, 2006; Cottee et al, 2019; Pastuzyn et al, 2018). Recently, it was shown that Arc/Arc1 can self-assemble into capsid-like structures that package and transport mRNAs into cultured neuronal cell lines and across synapses in vivo , constituting a novel mechanism of cell-cell communication (Ashley et al, 2018; Erlendsson et al, 2019; Pastuzyn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%